77‐GHz mmWave antenna array on liquid crystal polymer for automotive radar and RF front‐end module. Issue 2 (8th January 2019) - Kim, Sangkil; Rida, Amin; Lakafosis, Vasileios; Nikolaou, Symeon; Tentzeris, Manos M.
Abstract : This paper introduces a low‐cost, high‐performance mmWave antenna array module at 77 GHz. Conventional waveguide transitions have been replaced by 3D CPW‐microstrip transitions which are much simpler to realize. They are compatible with low‐cost substrate fabrication processes, allowing easy integration of ICs in 3D multi‐chip modules. An antenna array is designed and implemented using multilayer coupled‐fed patch antenna technology. The proposed 16 × 16 array antenna has a fractional bandwidth of 8.4% (6.5 GHz) and a 23.6‐dBi realized gain at 77 GHz.